2019
DOI: 10.1103/physrevfluids.4.104201
|View full text |Cite
|
Sign up to set email alerts
|

Inertial migration of a deformable particle in pipe flow

Abstract: We perform fully Eulerian numerical simulations of an initially spherical hyperelastic particle suspended in a Newtonian pressure-driven flow in a cylindrical straight pipe. We study the full particle migration and deformation for different Reynolds numbers and for various levels of particle elasticity, to disentangle the interplay of inertia and elasticity on the particle focusing. We observe that the particle deforms and undergoes a lateral displacement while traveling downstream through the pipe, finally fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…This is evident from recent numerical studies where migration of capsules and deformable particles in straight vessels was considered in the presence of inertia. Migration toward the vessel centreline was noted in Alghalibi, Rosti & Brandt (2019) and Hur et al (2011), while off-centre equilibrium was reported in Kilimnik, Mao & Alexeev (2011), Krüger, Kaoui & Harting (2014) and Shin & Sung (2011).…”
Section: Migration Of Deformable Particles In Straight Vessels In Thementioning
confidence: 95%
“…This is evident from recent numerical studies where migration of capsules and deformable particles in straight vessels was considered in the presence of inertia. Migration toward the vessel centreline was noted in Alghalibi, Rosti & Brandt (2019) and Hur et al (2011), while off-centre equilibrium was reported in Kilimnik, Mao & Alexeev (2011), Krüger, Kaoui & Harting (2014) and Shin & Sung (2011).…”
Section: Migration Of Deformable Particles In Straight Vessels In Thementioning
confidence: 95%
“…[46][47][48][49] Only recently, inertial microfluidics of deformable cells has caught attention. 20,[50][51][52][53][54][55][56][57][58] Using two-dimensional numerical simulations, Shin and Sung 51 showed that the final equilibrium position for a given value of capsule elasticity varies with the Reynolds number. In their following work 54 they identified different types of capsule dynamics such as tank-treading, swinging, and tumbling.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed that the inertial lift force in the vicinity of the channel center scales as a cube of capsule radius. More recently, Alghalibi and colleagues 58 investigated cross-stream inertial migration of a soft particle in pipe flow. Interestingly, they found that irrespective of the particle's softness and the flow rate, the particle always ends up at the channel center for an initial particle diameter of 0.2 times the pipe diameter.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the distorted first normal stress difference that builds up around the particle leading to an oscillatory stretching around the particle as shown in Fig. 5c, see also [57]. The final equilibrium position of the particle is also shown to be independent of its initial condition for both the Newtonian and the Non-Newtonian fluid, as shown in Fig.…”
Section: Numerical Simulationsmentioning
confidence: 75%